Dynamics of elite power and the clash of media reform agendas in contemporary Zimbabwe: Paper presented at the Conference for Journalism Educators held on the 24th-28th of October 2009, Wits University Johannesburg SA. - Mugari, Zvenyika E. (Midlands State University, 2017)
The current political and media policy framework in the country has resulted in Zimbabwe ranking among the few most dangerous countries to practise journalism in. Reporters Sans Frontieres (2008 Press Freedom Index) state that: "Being a journalist in ... Zimbabwe (151st) - is a high risk exercise involving endless frustration and constant police and judicial harassment". Journalists continue to be harassed, arrested, tortured and unlawfully detained. This paper explores the emergence of policy elites and their role in influencing the evolution of media legislative policy framework that has been emerging in Zimbabwe since 2000. It considers how the bipolar political contestations between the two dominant political formations in the country polarised the policy-making environment with resultant problems sharply manifesting themselves in the way the media operated and related to the rest of society. The media laws that get passed from around 2001 were themselves a product of a political process deeply divided. This discussion focuses on the ideological contestations among different elites at such institutions as the University of Zimbabwe faculty of Media and Communication Studies and the Department of Mass Communications at Zimbabwe Polytechnic College, as they co-opted and were co-opted with other elites in government bureaucracies, media professions councils and other intellectuals in diverse fields of expertise to set different and at times conflictual agendas for media reform in the country. The paper employs Alford’s schema of Dominant, Challenging and Repressed interests to analyse various actors as they competed to determine and drive the ongoing media reform process in Zimbabwe. Over the past decade there has emerged three major elite coalition tendencies vis-à-vis media policy making in Zimbabwe. There emerged a clearly pro-regime policy lobby crystallising in the Media Ethics Commission set up by government in 2001 and a pro-libertarian coalition of media interest groups that congeal in the form of the Media Alliance of Zimbabwe. The paper seeks to establish the extent to which the policy-making process in Zimbabwe can be argued to be top-down and undemocratic. It reviews key research reports, commissioned or un-commissioned and conference documents, position papers by key interest groups as its evidence. Media content on important media policy related issues is also analysed to establish the role the media themselves played in facilitating or impeding popular participation in the media reform debates. The discussion hopes to raise questions about the democratic deficits inherent in the current media reform trajectory.